2018
DOI: 10.5114/hivar.2018.76375
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization of human immunodeficiency virus type 1 isolated in Bali, Indonesia in 2016

Abstract: Introduction: Bali is a famous tourism destination in Indonesia, and many international travelers from several foreign countries visit Bali. A large number of human immunodeficiency type 1 (HIV-1) infections was found; however, the genotypes of HIV-1 strains circulating in Bali has not yet been elucidated in detail. In addition, the information on HIV drug resistance (HIVDR) in Bali is limited. Material and methods: HIV-1 pol gene encoding 31 proteases (PR gene) and 37 reverse transcriptase (RT gene) as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…CD4 count was the easiest predictor factor of the degree of HIV symptoms, and this study showed its positive correlation with Capute score. In line with previous research obtained that there was a positive correlation between cognitive disorders with CD4 levels [9], [10], [11]. Positive correlation also found between CAT scores and CD4 count (r = 0.418 and p = 0.01).…”
Section: Discussionsupporting
confidence: 92%
“…CD4 count was the easiest predictor factor of the degree of HIV symptoms, and this study showed its positive correlation with Capute score. In line with previous research obtained that there was a positive correlation between cognitive disorders with CD4 levels [9], [10], [11]. Positive correlation also found between CAT scores and CD4 count (r = 0.418 and p = 0.01).…”
Section: Discussionsupporting
confidence: 92%
“…CRF01_AE, the second predominant circulating CRF accounting for 5% of infection cases worldwide in 2004-2007, is responsible for the vast majority of infections in Southeast Asia, including several regions in Indonesia. [3][4][5][6][7] Subtypes and CRFs may differ in the rates of disease progression and viral transmission.…”
Section: Textmentioning
confidence: 99%
“…12 Previous studies that focused on Gianyar Regency and Denpasar city in Bali identified CRF01_AE as the major cause of infection, and major drug resistance mutations (DRMs) in the RT gene were detected in 25.8% of ART-experienced individuals. 7 The genotypic characteristics of HIV-1 circulating in tourism-concentrated regions may differ from those in regions less popular for tourism; however, limited information is currently available on HIV-1 subtypes and the prevalence of DRM outside South Bali. Therefore, the present study aimed to Successfully amplified viral genes were then subjected to a sequence analysis performed by Macrogen Japan (http://www.macrogen-japan.co.jp).…”
Section: Textmentioning
confidence: 99%
“…1 As many other countries, HIV infection in Indonesia is mainly caused by HIV type 1 (HIV-1) group M. There are nine subtypes (A, B, C, D, F, G, H, J, and K), as well as circulating recombinant forms (CRFs) and unique recombinant forms (URFs), within the group M. 3 Several studies have reported the dominance of HIV-1 CRF01_AE in several Indonesian regions. [4][5][6][7][8][9][10] As an effort to address the HIV epidemic, Ministry of Health of Indonesia implemented antiretroviral therapy (ART) under national guideline. First-line ART regimen recommended contains two nucleoside reverse transcriptase (RT) inhibitors (NRTIs) and one non-nucleoside RT inhibitor (NNRTI).…”
Section: Introductionmentioning
confidence: 99%
“…12 The emergence of acquired drug resistance (ADR) in treatment-experienced individuals and transmitted drug resistance (TDR) in treatment-naive individuals residing in several Indonesian regions, including Surabaya, Riau, Bali, and Maumere, has been previously described. [5][6][7][8][9][10] The TDR might disrupt effectiveness of treatment, resulting in unfavorable clinical outcomes. 13 Therefore, it is important to monitor the emergence of TDR by a continuous surveillance in order to secure long-term and stable ART in Indonesia.…”
Section: Introductionmentioning
confidence: 99%